Knowledge, Practice and Perception regarding Micronutrient Powder among Mothers attending a Tertiary Hospital in Chitwan District, Nepal - Shrestha, Niki; Shah, Sanjeeb; Aryal, Dilip; Chaulagain, Prashant; Basnet, Kalyan Bikram; Bhattarai, Roshan Raj (Annapurna Journal of Health Sciences, 2026)
Introduction: Under-nutrition causes approximately 3.5 million deaths of children under five annually in developing nations, with many of these deaths linked to micronutrient deficiency. Thus, the purpose of the study is to assess the knowledge, practice and perception of mothers with children 6-23 months regarding micronutrient powder (Baal Vita) at tertiary hospital of Chitwan district.Methods: A cross-sectional study was conducted in Chitwan Medical College Teaching Hospital among mothers of children age 6-23 months from June 10, 2025 to 30 June, 2025. Convenience sampling method was used to select the sample of 380. A structured questionnaire was used to collect data through face to face interview with mothers. Descriptive analysis was performed using IBM SPSS version 20. Ethical approval for this study was taken from Chitwan Medical College Institutional Review Committee.Results: Out of 380 mothers, 290(76.3%) had heard of micronutrient powder and out of 290 respondents, 124(42.7%) respondents’ child accepted micronutrient powder and of those who did not accept, the reason was bitter taste 52(31.3%). Most of the respondents 266(91.7%) prepared micronutrient powder by mixing with food. More than half of the mothers 154(53.1%) perceived health benefit of micronutrient powder to their child.Conclusions: Most of the mothers had knowledge about the micronutrient powder; however in practice, child’s acceptance of micronutrient powder was low because of its bitter taste and perceived health benefits of it in their child was also low among the mothers.